1986
DOI: 10.1177/030802268604900904
|View full text |Cite
|
Sign up to set email alerts
|

Biological Sciences in Occupational Therapy Education: A Review Carried Out at One Occupational Therapy School

Abstract: This paper looks at pre-entry examination passes in the biological sciences at '0' and 'A' level and the effect that these have on occupational therapy students' performance in anatomy and physiology in the first year of the course at the Liverpool College of Occupational Therapy. Results suggest that there was no significant relationship between the two in six out of the seven years studied (1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results of this study support the OT specific research before it that found no significant correlations between pre-admission qualifications and final degree outcomes for undergraduate OT students (Howard & Jerosch-Herold, 2000;Howard & Watson, 1998;Posthuma & Noh, 1990;Tyldesley, 1986). It is worth noting however, that the cumulative evidence from these studies relates to students enrolled onto baccalaureate degrees.…”
Section: Pre-admission Academic (Cognitive) Data and Final Degree Clasupporting
confidence: 79%
See 2 more Smart Citations
“…The results of this study support the OT specific research before it that found no significant correlations between pre-admission qualifications and final degree outcomes for undergraduate OT students (Howard & Jerosch-Herold, 2000;Howard & Watson, 1998;Posthuma & Noh, 1990;Tyldesley, 1986). It is worth noting however, that the cumulative evidence from these studies relates to students enrolled onto baccalaureate degrees.…”
Section: Pre-admission Academic (Cognitive) Data and Final Degree Clasupporting
confidence: 79%
“…Results found the A-Level group yielded significantly better scores in an initial A&P exam but that this difference did not transcend to the end of year A&P exam results. With the exception of one academic year, the study found no significant difference between the two groups, concluding that while a science qualification may be helpful in the initial stages, it is unlikely to be an essential prerequisite for OT training (Tyldesley, 1986).…”
Section: United Kingdommentioning
confidence: 75%
See 1 more Smart Citation
“…Two studies looked at the impact of A-level biology on academic performance in occupational therapy education. Tyldesley (1986) analysed seven cohorts of occupational therapy student data (n = 357) from 1977 to 1984 to see whether those students who entered with A-level biology gained higher grades in anatomy and physiology courses compared with students admitted with an O-level in this subject or those with no qualification in biology at all. The results showed no consistent advantage to having an A-level in biology on entry, although the statistical analysis of these data was limited to bivariate analysis.…”
Section: United Kingdommentioning
confidence: 99%
“…The results showed no consistent advantage to having an A-level in biology on entry, although the statistical analysis of these data was limited to bivariate analysis. Tyldesley (1986) had three categories of students in the study, but examined the differences only between the two groups who had some school biology on entry. The third 'no biology' group was not included in the data analysis, which was surprising because many mature students enter occupational therapy programmes without this subject and their performance on the course would have been interesting to explore.…”
Section: United Kingdommentioning
confidence: 99%